2007
DOI: 10.1021/jo0711337
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Pot Synthesis of 6-Monosubstituted and 6,12-Disubstituted 5,11-Dihydroindolo[3,2-b]carbazoles and Preparation of Various Functionalized Derivatives

Abstract: A facile three-stage, one-pot approach for the synthesis of a variety of novel 6-monosubstituted and 6,12-disubstituted 5,11-dihydroindolo[3,2-b]carbazoles, in moderate to good yields (20-50%), has been developed, based on the condensation of an indole and an aldehyde with a catalytic amount of iodine, followed by an acid-catalyzed intramolecular cyclization with an ortho ester. The parent indolo[3,2-b]carbazoles (ICZs) could be converted to various functional derivatives. Both N-alkylation and N-arylation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…INC is known to show strong blue fluorescence under irradiation by ultraviolet (UV) light. In recent years, there have been some reports on the preparation and characterization of derivatives of INC. [16][17][18][19][20][21][22][23][24][25] In particular, Hu et al 21 have reported 1,7-dinaphtylindolo [3,2-b]carbazole, which showed excellent hole-transport properties in light-emitting diodes. Later, the first organic field-effect transistors using N-alkylated INC as an active layer was successfully fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…INC is known to show strong blue fluorescence under irradiation by ultraviolet (UV) light. In recent years, there have been some reports on the preparation and characterization of derivatives of INC. [16][17][18][19][20][21][22][23][24][25] In particular, Hu et al 21 have reported 1,7-dinaphtylindolo [3,2-b]carbazole, which showed excellent hole-transport properties in light-emitting diodes. Later, the first organic field-effect transistors using N-alkylated INC as an active layer was successfully fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, ICZ can easily be synthesized in large scale yield with two simple reaction steps,10 and the purification process can easily be realized by the physical vapor transport (PVT) method 11. In addition, the nitrogen heteroatom of ICZ provides two positions (2,8‐ and 3,9‐) for additional displacements with functional groups to improve the molecular conjugation and modify the material's solubility and chemical tunability 12. The two reactive positions allow controllable synthesis of various polymers with good processability and performance 13.…”
Section: Summary Of Crystal Packing and Performance Of Heteropentacenmentioning
confidence: 99%
“…The rich chemistry of the methylene-bridged LOPPs has encouraged many researchers to synthesize various types of LOPPs containing main-group elements, such as B, [21,22] Si, [23][24][25][26][27] N, [28][29][30][31][32] P, [33][34][35] S, and Se, [36][37][38] as the bridging moieties (Scheme 3). These main-group elements significantly affect the electronic structure of the parent p-conjugated skeleton.…”
Section: Ladder Oligo(p-phenylene)s (Lopps)mentioning
confidence: 99%